Evaluation of replacing the existing diagnostic strategy for Neisseria gonorrhoeae and Chlamydia trachomatis infections with sole molecular testing of urine specimens in a sexually transmitted infection clinic setting. Issue 5 (29th April 2009) - Ho, M K; Lo, J Y C; Lo, A C T; Cheng, F K; Chan, F K
Abstract : Objectives: To evaluate nucleic acid testing of urine specimens against conventional Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) tests in genital swab specimens in a sexually transmitted infection (STI) clinic setting. Methods: Genital swab and urine samples were collected from attendees of public STI clinics in Hong Kong from May to June 2007. Swab specimens were subjected to on-site Gram stained microscopy and inoculation onto modified Thayer–Martin medium for NG culture before laboratory processing. CT PCR on genital swabs was performed by the Roche Cobas Amplicor test. Urine samples were tested for CT and NG by the Aptima Combo 2 (AC2) assay. Results: Data from 414 patients were analysed. The sensitivity and specificity of AC2 for NG were 100% (35/35) and 98.4% (373/379), respectively, with culture of genital swab specimens as standard. On-site microscopy provided timely results for empirical antimicrobial therapy, whereas culture yielded bacterial isolates for susceptibility testing and typing studies. Regarding CT, using Amplicor on genital swab specimens as reference, the sensitivity and specificity of AC2 were 98.7% (78/79) and 97.5% (313/321), respectively. Amplicor yielded uninterpretable results in 14 specimens due to PCR inhibitors. Conclusions: The current STI clinic and laboratory practices were practical and useful for clinical management, even though favourable results were obtained with the AC2 assay, which had streamlined laboratory workflow. The use of a molecular testing strategy may be cost-effective with microscopy and culture being targetted for patient groups with the highest expected yield of positive results.